PROTOTYPE OF PERSONAL SAFE SECURITY DEVICE USING AN ARDUINO UNO-BASED FINGERPRINT SENSOR WITH SMS NO-TIFICATION - Penawati; Lalu Puji Indra Kusuma (JATISKOM : Jurnal Aplikasi Teknologi Informasi dan Sains Komputer, 2024)
As we know, a safe is a place to store money and other valuables and important items. Because the security of the safe is currently still minimal and still uses old security methods, making it easy for criminals to break into it or damage it, to prevent such crimes, adequate security is needed as well as sophisticated and modern tools in keeping up with current technological developments so that the security system is more secure. In this thesis, the author makes an alternative solution to the existing problem, namely a prototype of a personal safe security device using a fingerprint sensor that has the ability to protect a personal safe by being equipped with SMS notifications, thereby increasing security for users. The design and manufacture of a prototype of a personal safe security device using a fingerprint sensor with SMS notifications uses research and development (R&D), which is a process or steps to develop a new product or improve an existing product. The results, or output, of the tool that the author designed are a prototype of a personal safe security device using a fingerprint sensor with SMS notifications.